The Political Legitimacy of the Communist Party of China From the Perspective of Constitution (Asian Journal of Social Science Studies, 2018)
The Communist Party of China’s political legitimacy is a result which is based on its unique advanced and excellent quality, combines the basic principles of Marxism-Leninism with the concrete practice of China, and gains the support of Chinese people because of leading Chinese people to overthrow the reactionary rule to establish a new completely people's political regime and putting forward the line and route which conform to the development direction and requirement of Chinese social history. That is to say, this is the objective result of the Chinese people's sincere choice and commitment, and then confirmed in the national Constitution, which condenses the fundamental will and interests of the Chinese people. The process of Chinese Constitution establishment and the Constitution’s ideas and norms, both of them provide sufficient legal basis for the political legitimacy of the Communist Party of China. In that way, the continuation of the Communist Party of China’s political legitimacy-leadership and governance-must adhere to the rule of Constitution.